ASUPAN ZAT GIZI MAKRO DAN SERAT MENURUT STATUS GIZI ANAK USIA 6-12 TAHUN DI PULAU SULAWESI - Agustina, Wulan; Jus’at, Idrus; Mulyani, Erry Yudhya; Kuswari, Mury (Jurnal Gizi dan Pangan, 2015)
ABSTRACTThe aimed of this study was to determine the differences intake of macro-nutrients (protein, fat, carbohydrates) and fiber with respect to their nutritional status of children aged 6-12 years. This study was used secondary data Riskesdas 2010. The number of subjects was 2,987 children aged 6-12 years in Sulawesi Island. Body Mass Index for Age (BMI/U) was used to measure the nutritional status. Independent sample t-test and analysis of variance were applied to answer the research questions. The result showed that most of subjects were male (58.7%), living in rural areas (50.2%), and with low economic status (54.1%). In regard to protein intake, most of the children age 6 years was about 80-99% Recommended Dietary Intake (RDA). On the contrary, most of children 7-9 years and 10-12 years were below 70% RDA. There were no differences intake of macro-nutrients (protein, fat, carbohydrates) and fiber to the nutritional status of children aged 6-12 years (p>0.05). This study found that most of the children were suffering macro-nutrients intake regardless their nutritional status. Therefore, we need to have a good program to monitor nutritional status of school children.Keywords: nutrient intake, nutritional status, school age children 6-12 yearABSTRAKPenelitian ini bertujuan untuk mengetahui perbedaan asupan zat gizi makro (protein, lemak, karbohidrat) dan serat terhadap status gizi pada anak usia 6-12 tahun. Penelitian ini menggunakan data sekunder Riskesdas 2010 dengan pendekatan cross-sectional. Subjek penelitian adalah anak usia 6-12 tahun dengan status gizi kurus, normal, dan gemuk menurut IMT/U di Pulau Sulawesi tahun 2010 berjumlah 2.087 orang. Pengujian statistik menggunakan independent sample t-test dan Anova. Sebagian besar subjek berjenis kelamin laki-laki (58,7%), tinggal di perdesaan (50,2%), dan berstatus ekonomi rendah (54,1%). Rata-rata asupan protein pada kelompok umur 6 tahun termasuk kategori sedang (80-99% AKG) namun pada usia 7-9 tahun dan usia 10-12 tahun termasuk kategori defisit (<70% AKG). Tidak terdapat perbedaan asupan zat gizi makro dan serat terhadap status gizi (IMT/U) di Pulau Sulawesi (p>0,05). Penelitian ini menemukan adanya keberagaman asupan dan status gizi anak usia sekolah. Oleh karenanya, diperlukan program pemantauan status gizi secara rutin di sekolah.Kata kunci: anak usia 6-12 tahun, asupan zat gizi, status gizi